UJI AKTIVITAS ANTIBAKTERI DARI EKSTRAK ETANOL DAUN PERIA LAUT (Colubrina Asiatica L.) TERHADAP BAKTERI STAPHYLOCOCCUS AUREUS DAN ESCHERICHIA COLI - Firdaus Fahdi; Harwitavia Harwitavia; Herviani Sari (Jurnal Penelitian Farmasi & Herbal, 2019)
The discovery of new antibiotic drugs is getting more and more reactive. The plant of the peria laut leaf is one of the drugs that is often used as a traditional medicine and contains bioactive compounds of polyphenols, flavonoids, and saponins, which can inhibit antibacterial growth. Purpose of this study was to determine the antibacterial activity of ethanol extract of peria laut leaves (Colubrina asiatica L.) against Staphylococcus aureus and Escherichia coli bacteria. Method the experimental, of the sample used was concentrated marine peria laut leaf extract of 25mg/ml, 50mg/ml, 75mg/ml, 100mg/ml, 200mg/ml, 300mg/ml, 400mg/ml, and 500mg/ml, positive control of amoxicillin tablet 500 mg, negative control of dimethylsulfoxide with the method of disc diffusion testing using media Nutrient Agar. Results the showed thet the peria laut leaf extract positively contained bioactive alkaloid compounds, flavonoids, saponins, steroids, and tannins, and had inhibitory effects on Staphylococcus aureus and Escgerichia coli bacteria with various concentrations which had been tested on the average area of the highest inhibition zone of 18,6 mm in Staphylococcus aureus bacteria, and 10,2 mm in Escherichia coli bacteria. Conclusion peria laut leaf extract (Colubrina asiatica L.) has antibacterial activity against Staphylococcus aureus and Escherichia coli bacteria in the most inhibitory zone at a concentration of 500mg/ml with a diameter of 18,6 in Staphylococcus aureus bacteria and 10,2 in Escherichia coli.